Dynamic poverty processes and the role of livestock in Peru - Kristjanson, Patricia M.; Krishna, A.; Radeny, Maren A.O.; Kuan, J.; Quilca, G.; Sánchez Urrelo, A. (Food and Agriculture Organization of the United Nations, 2007)
This is the 39th of a series of Working Papers prepared for the Pro-Poor Livestock Policy Initiative (PPLPI). The purpose of these papers is to explore issues related to livestock Development in the context of poverty alleviation. Livestock is vital to the economies of many developing countries. Animals are a source of food, more specifically protein for human diets, income, employment and possibly foreign exchange. For low income producers, livestock can serve as a store of wealth, provide draught power and organic fertiliser for crop production and a means of transport. Consumption of livestock and livestock products in developing countries, though starting from a low base, is growing rapidly. A community-based qualitative-quantitative poverty methodology called the Stagesof-Progress approach was used to assess household poverty dynamics and the role of livestock in 40 communities and over 3,800 households representing two different highland regions of Peru (Puno and Cajamarca). Key to the approach used was to define with the participating communities a common understanding of poverty. The major reasons for movements into or out of poverty were elicited at both the community and household-level, and in particular, the role that livestock play in the different pathways was examined.